The Response of the Participation Rate to Public Islamic Universities: Empirical Evidence from Central Java, Indonesia - M. Sugeng Sholehuddin; Moh. Nurul Huda; Miftah Mucharomah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2020)
The current study aims to investigate the participation rate of people in Central Java, Indonesia to public Islamic universities in the period of 2015-2017, i.e. perceptions, factor analysis, and public interest. Grounded in mixed methods, data were collected through questionnaires, interviews, and documentation. A total of 24,903 parents of prospective students situated in the areas of three public Islamic universities in Central Java became the research population. Proportionate random sampling was undertaken to yield 268 research participants. Study findings promote that firstly, the participation rate of people in Central Java to the government-funded Islamic universities reached 16.9 in 2016, 66.6 in 2017, and 67.3 in 2018 for percentages. Secondly, the average public perception rate to the public universities under the supervision of the Ministry of Religious Affairs was reported at the good criterion well with a score of 22.9. The majority of people demonstrated a positive view of the harmony of science and religious studies. Afterward, the average internal and external factors influence interest in the admission of the Islamic universities with an average score of 69.7 at the good enough level. Lastly, the public interest of Central Java in the universities achieved a score of 35.5 at the quite high criterion. This study also demonstrates that the public Islamic university’s services have provided excellent infrastructure, teaching staff, and student academic services. Nonetheless, various improvements are required, e.g. information technology and improvement of quality graduates to compete with other public universities.